2015
DOI: 10.1155/2015/704390
|View full text |Cite
|
Sign up to set email alerts
|

Xueshuan Xinmaining Tablet Treats Blood Stasis through Regulating the Expression of F13a1, Car1, and Tbxa2r

Abstract: Xueshuan Xinmaining Tablet (XXT), the Chinese formula, has long been administered in clinical practice for the treatment of cerebral thrombosis and coronary heart disease. In this study, we aimed to study the effect and the molecular mechanism of activating blood circulation and removing blood stasis. Rat models of cold coagulation blood stasis were induced with ice-water bath and epinephrine to assess the amelioration of blood stasis by XXT. Microarray technique was used to identify gene expression from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Modern medical research has shown that the occurrence of BSS is closely related to hemorheology abnormalities and coagulation disorders (Hayakawa et al, ; Szymanska, Saccenti, Smilde, & Westerhuis, ; Zhang et al, ). Our experimental results showed that the whole blood and plasma viscosity of BSS rats were significantly increased, indicating that blood running resistance was increased, which was in accordance with the previous reports (Dang et al, ; Zhang et al, ). Additionally, blood coagulation function is another crucial parameter for BSS evaluation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Modern medical research has shown that the occurrence of BSS is closely related to hemorheology abnormalities and coagulation disorders (Hayakawa et al, ; Szymanska, Saccenti, Smilde, & Westerhuis, ; Zhang et al, ). Our experimental results showed that the whole blood and plasma viscosity of BSS rats were significantly increased, indicating that blood running resistance was increased, which was in accordance with the previous reports (Dang et al, ; Zhang et al, ). Additionally, blood coagulation function is another crucial parameter for BSS evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…Dang et al, 2015;Zhang et al, 2015). Additionally, blood coagulation function is another crucial parameter for BSS evaluation.…”
mentioning
confidence: 99%
“…Xueshuan Xinmaining Tablet (XXT), a Chinese traditional compound medicine composed of ten herbs, possesses the activities of promoting blood circulation and removing blood stasis. 1 It is recorded in the Chinese Pharmacopoeia (2015 edition) and has been clinically applied for the treatment of cerebral thrombosis and coronary heart disease for at least een years. 2,3 In our previous studies, we have reported that XXT could treat blood stasis through regulating related genes and proteins or endogenous metabolite pathways.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In our previous studies, we have reported that XXT could treat blood stasis through regulating related genes and proteins or endogenous metabolite pathways. 1,4,5 The multitarget mechanism is closely related to the variation in the chemical components contained. We have reported the comprehensive component screening of XXT based on UPLC/Q-TOF-MS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation